A Phaseolus vulgaris Diversity Panel for Andean Bean Improvement. Issue 5 (1st September 2015) - Cichy, Karen A.; Porch, Timothy G.; Beaver, James S.; Cregan, Perry; Fourie, Deidre; Glahn, Raymond P.; Grusak, Michael A.; Kamfwa, Kelvin; Katuuramu, Dennis N.; McClean, Phil; Mndolwa, Eninka; Nchimbi‐Msolla, Susan; et al.
ABSTRACT: Dry beans ( Phaseolus vulgaris L.) of the Andean gene pool, including red mottled, kidney, cranberry, and yellow seed types are important in Africa and the Americas. Andean dry bean breeding gains have lagged behind those of Mesoamerican beans. This difference may result from a narrower genetic base in the Andean gene pool and reduced breeding efforts. The objective of this research was to establish, genotype, and phenotype a panel of bean germplasm to be used for Andean dry bean breeding. An Andean diversity panel (ADP) was assembled, consisting of 396 accessions and including important cultivars, breeding lines, and landraces that originate mostly from Africa, the Caribbean, and North and South America. The panel was genotyped using the Illumina BARCBean6K_3 SNP BeadChip. The population contained two subgroups: Andean and Mesoamerican bean germplasm. The ADP was comprised of 349 Andean, 21 Mesoamerican, and 26 Andean–Mesoamerican admixed accessions. Most admixed lines came from Africa (12 accessions) and the Caribbean (five accessions). Association mapping was conducted for determinacy. Significant single‐nucleotide polymorphism (SNP) trait associations were found on chromosome Pv01, with the most significant SNP marker being 3.1 kb from the Terminal Flower 1 PvTFL1y gene. The ADP was evaluated for numerous traits in field trials in the United States and Africa. Variability was found for resistance to rust, angular leaf spot and common bacterial blight diseases; tolerance to low soil fertility; cooking time; and other traits that can be used to improve Andean bean germplasm for Africa and the Americas.